The Role of Islamic Religius Education In Realizing Justice And Peace In Indonesia - ilham Muhammad Ilham Nurhakim; Shintia Shintia; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Abstract - The role of Islamic religious education in realizing justice and peace in Indonesia has been going on for a long time, along with the entry of Islam in Indonesia. However, that does not mean the role is completely finished. It is widely emphasized that there are still acts of anarchy, injustice, intolerance and other destructive acts. In this void, it is interesting to study the role of religious education in realizing justice and peace. This study aims to find a new light about Islamic education that can be used as a standard for developing religious education in an effort to create peace in Indonesia. This study uses a qualitative approach using in-depth interviews, participatory observation, and documentation as data collection methods. The results of this study reveal that first, religion has a fundamental role in the existence and survival of the Indonesian nation. Second, in the era of regional autonomy and reform, it was found that there was a significant improvement in the quality of religious education which was carried out consistently. Third, post-reform, religious education plays an important role as a forum for building the moral values of human resources to create a sense of justice and peace in Indonesia.